Laccase Production Optimization from Recombinant E. coli BL21 Codon Plus Containing Novel Laccase Gene from Bacillus megaterium for Removal of Wastewater Textile Dye - Zannara Mustafa; Ikram ul Haq; Ali Nawaz; Abdulrahman H. Alessa; Muhammad Nauman Aftab; Ahmad A. Alsaigh; Aziz ur Rehman (Molecules, 2024)
The aim of the present research was the efficient degradation of industrial textile wastewater dyes using a very active cloned laccase enzyme. For this purpose, potent laccase-producing bacteria were isolated from soil samples collected from wastewater-replenished textile sites in Punjab, Pakistan. The laccase gene from locally isolated strain LI-81, identified as Bacillus megaterium, was cloned into vector pET21a, which was further transformed into E. coli BL21 codon plus. The optimized conditions for the increased production of laccase include fermentation in a 2% glucose, 5% yeast extract and 250 mg/L CuSO4 medium with pH 7.5; inoculation with 5% inoculum; induction with 0.1 mM IPTG at 0.5 O.D.; and incubation for 36 h at 37 °C. The crude enzyme produced was employed for the removal of commercially used textile dyes. The dyes were quickly precipitated under optimized reaction conditions. Rose bengal, brilliant green, brilliant blue G, Coomassie brilliant blue R and methylene blue were precipitated at rates of 10.69, 54.47, 84.04, 78.99 and 7.40%, respectively. The FTIR and UV–Vis spectroscopic analyses of dyes before and after confirmed the chemical changes brought about by the cloned laccase that led to the dye removal.